2007
DOI: 10.1177/1363459307077547
|View full text |Cite
|
Sign up to set email alerts
|

Chronic illness and health-seeking information on the Internet

Abstract: By using the theories of help-seeking behavior and health-information seeking, this article demonstrates the relationship between chronic illness, retrieving health information from the Internet and changing health behavior. Research on the impact of health information on the Internet and changing health behavior is fairly new, given the growth of the Internet in recent years. Using US data on Internet use within the US population, multiple regression analysis was performed to explore the relationships between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
139
2
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(155 citation statements)
references
References 36 publications
8
139
2
6
Order By: Relevance
“…[1][2][3] The internet is a promising means of delivering health information to patients 4 and allowing them better access to healthcare systems. 5 Additionally 70-80% of Americans use the internet.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The internet is a promising means of delivering health information to patients 4 and allowing them better access to healthcare systems. 5 Additionally 70-80% of Americans use the internet.…”
Section: Introductionmentioning
confidence: 99%
“…Spink et al [23] characterized healthcare-related queries issued to Web search engines, and showed that users were gradually shifting from general-purpose search engines to specialized Web sites for medical-and health-related queries. Ayers and Kronenfeld [1] also utilized log data on Web use, and perform a multiple regression analysis to explore the relationship between chronic medical conditions and frequency of Web use, as well as changes in health behavior due to frequency of Web use. Their findings suggest that it was not the presence of one particular chronic illness, but rather the total number of chronic conditions that determines the nature of Web use.…”
Section: Related Workmentioning
confidence: 99%
“…Scholars suggest that younger people tend to seek information more actively than older people (Mayer et al, 2007;Rutten et al, 2005). The frequency of older adults' internet usage for health information is lower relative to younger users (Ayers & Kronenfeld, 2007). One study reveals that 60% of older adults use the Internet to find health care information, compared to 70% for middle-aged and younger (Miller & Bell, 2012).…”
Section: The Effects Of Age and Gendermentioning
confidence: 99%